Pengaruh Pengetahuan Santri pada Produk Reksadana Syariah terhadap Minat Santri Berinvestasi Direksadana (Studi Kasus Mahasantri Pondok Pesantren Sunan Drajat Lamongan Jawa Timur) - Latifatul Kharisma; Ahmad Iwan Zunaih; Zakiyatul Abidah (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2019)
This research is motivated by the rapid and dynamic development of the capital market investment world. One of the capital market products that is widely known by the public is mutual funds. In the development of mutual funds, there have been sharia mutual funds that provide broad investment alternatives, especially for Muslim investors. but based on the facts, behind the hustle and bustle of mutual fund investment activities in the world, only a few students of the Sunan Drajat Islamic Boarding School have invested in mutual funds. There are several factors that cause students to have no interest in investing through sharia mutual funds. Among several existing factors, researchers are more interested in examining the knowledge of students about sharia mutual funds. The purpose of this study is to determine whether or not there is an influence of knowledge of students at the Sunan Drajat Islamic Boarding School on sharia mutual funds products can affect students' interest in investing in mutual funds. The sampling technique used in this study is Convinience Sampling with a population of students of the Sunan Drajat Islamic Boarding School.. Data collection using a questionnaire instrument. Testing the instrument using the validity test and reliability test through the computer program SPSS version 16.0. Test assumptions using normality test and linearity test. The data analysis technique used is a simple linear regression test. The assumption test in this study uses the t test and the coefficient of determination. Based on the results of a simple linear regression test, the t-count value is 9.768 which exceeds the t-table value of 2.011, which means that students' knowledge of Islamic mutual funds products has an effect on students' interest in investing in mutual funds. The results of the coefficient of determination test obtained an R value of 0.816 and an R Square of 0.665, which means that students' knowledge of Islamic mutual funds products has an effect of 66.5% on students' interest in investing in mutual funds. The remaining 33.5% is influenced by other variables.